Comparative study between Reid’s colposcopic index score and Swede’s score in women with cervical precancerous lesions - Anjum, Shazia; Sweta; Saini, Oshan; Saini, Vandana (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Background: Colposcopic indexes including Reid’s index and Swede’s score were developed to make the colposcopy more objective. The aim of this study was to compare two widely used colposcopic indices Reid’s index and Swede’s score for the detection of premalignant lesions of the cervix. Methods: This prospective observational study was conducted on 125 women who attended gynecology OPD with gynecological complaints in June-2018 to July-2019 in the department of obstetrics and gynecology at Hindu Rao Medical College New Delhi over a period of one year. Colposcopic examination was done in all patients RCI score and Swede’s score were calculated from the colposcopic findings. Biopsy was taken and histopathology results were recorded. Results: Majority of women enrolled in the study were between 41-50 years (36%), 88.00% were married staying with husband. Around 41.60% were illiterate, it was observed that majority of women 70.40% had first sexual inter course at ≤18 years. There was an excellent correlation between RCI and Swede’s score p value was <0.001. Larger size of lesions was associated with malignant cases. Conclusions: Swede’s score and RCI score have good correlation in detecting cervical cancer. However, Swede’s score is better than RCI score for predicting cervical intraepithelial neoplasia 1 (CIN 1).